Auto Checker of Higher Mathematics - an element of mobile cloud education - Tetyana I. Zhylenko; Nataliia S. Martynova; Irina A. Shuda; Yevhenii A. Chykalov; Danyla A. Kuzmuk (Academy of Cognitive and Natural Sciences, 2020)
We analyzed the main cloud services in the article. We also described the main contribution of mobile cloud technology to education. The article presents the author's development from the field of mobile cloud education in higher mathematics. The design architecture of this application is described in detail: QR generator and scanner, authorization, sending tasks. Block diagrams and images are presented that clearly demonstrate the operation of the application. We showed an example of solving the integral from the section of integral calculus for higher mathematics and showed how to download the answer in the form of a QR code and find out whether it is correct or incorrect (this can be seen by the color on the smart phone screen). It is shown how this technology helps the teacher save time for checking assignments completed by students. This confirms its effectiveness. Such an application provides students and teachers with the ability to store and process data on a cloud computing platform.